(untitled) (Bangladesh Journal of Zoology, 2015)
Seasonal and sex wise occurrence of endoparasitic helminths were observed from sample collected round the year between January 2005 and December 2007. Some 2667 hilsa (male 288 and female 2379) were sampled from freshwater, brackish water and marine habitats. Fourteen species/genera of endohelminth parasites detected from hilsa were Faustula brevichrus, F. ilishii, F. gangeticus, Aphanurus stossichi, Lecithaster indicus, Ilisha parthenogenetica (plercercoid), Otobothrium ilisha (plercercoid), Acanthosentis indica, A hilsai, Goezia bangladeshi, Capillaria sp., Hysterothylacium sp., Camallanus sp. and Porroceacum sp. Out of these 14 helminths, 6 (Faustula spp. Aphanurus stossichi, Lecithaster indicus, Ilisha parthenogenetica, Acanthosentis spp., and Goezia bangladeshi,) had the status of component parasite (prevalence above 10%). Each species of component parasite has shown its own pattern of distribution over seasons and seasonal distribution of component parasites was found to be different between habitats of the hilsa. In freshwater, the spring and winter samples were found not significantly different from each other. But in summer and autumn, there was a significant difference among each other and between spring or winter. In brackish water mean parasite burden in spring was significantly different from other seasons. In marine hilsa the intensity of parasites in all the four seasons were different from each other. The female fishes were found to be more vulnerable to infection irrespective of the habitats of the host fish, though the differences were little. Bangladesh J. Zool. 41(2): 153-163, 2013